2006
DOI: 10.1016/j.neubiorev.2006.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Development of structure and function in the infant brain: Implications for cognition, language and social behaviour

Abstract: Recent advances in cognitive neuroscience have allowed us to begin investigating the development of both structure and function in the infant brain. However, despite the rapid evolution of technology, surprisingly few studies have examined the intersection between brain and behaviour over the first years of life. Even fewer have done so in the context of a particular research question. This paper aims to provide an overview of four domains that have been studied using techniques amenable to elucidating the bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 149 publications
7
49
0
1
Order By: Relevance
“…In babies, such deficits strongly predict older-age deficits in language and reading abilities (3,33). A study that showed that adaptive computer training aimed at reducing acoustic temporal integration times significantly improved speech and language comprehension abilities of children with specific language impairments further supports the argument that there is a causal relationship between the speed of successive-signal processing and an individual's aural language abilities (34).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In babies, such deficits strongly predict older-age deficits in language and reading abilities (3,33). A study that showed that adaptive computer training aimed at reducing acoustic temporal integration times significantly improved speech and language comprehension abilities of children with specific language impairments further supports the argument that there is a causal relationship between the speed of successive-signal processing and an individual's aural language abilities (34).…”
Section: Discussionmentioning
confidence: 82%
“…The auditory cortex plays a critical role in the perception of time-varying features of aural speech and of other complex acoustic stimuli. In humans, speech comprehension is correlated with responses of cortical neurons to temporal envelopes of speech (1), and individuals with impaired language abilities have impaired successive signal evoked cortical responses (2,3).…”
mentioning
confidence: 99%
“…And last, during this fourth stage (between 8 and 12 months), the frontal, parietal, and occipital lobes continue myelination, furthering the development of sensory systems and conscious thought Downloaded by [The University of Manchester Library] at 08:55 15 December 2014 (Paterson et al, 2006). Soon the infant will be able to plan and carry out a series of actions to get what he or she wants more effectively.…”
Section: Stage 4: 8 To 12 Monthsmentioning
confidence: 99%
“…Recent advances in cognitive neuroscience have allowed researchers to investigate the structure and function of the infant brain (Paterson et al, 2006). However, few studies or articles have examined the intersection between brain and behavior over the first few years of life or attempted to synthesize the research on human neural development (Webb et al, 2001).…”
Section: Application To Researchmentioning
confidence: 99%
“…Young children have been noted to make tremendous advances in pretend play when the play occurs with social partners when compared to solitary pretend play. Joint attention skills also contribute significantly to language acquisition and development (Baldwin, 1993;Mundy & Gomes, 1998;Paterson, Heim, Friedman, Choudhury, & Benasich, 2006). The social exchanges facilitated through joint attention help infants understand the nuances of spoken language, experiment with communication modalities, and gain exposure to concepts that were previously outside of awareness.…”
Section: Attentionmentioning
confidence: 99%